New Wave Behaviours of the Generalized Kadomtsev-Petviashvili Modified Equal Width-Burgers Equation - Ali, Karmina K.; Yilmazer, Resat; Bulut, Hasan; Yokus, Asif (Natural Sciences Publishing, 2022)
In this article, we applied two different methods namely as the (1/G? )-expansion method and the Bernoulli sub-equation method to investigate the generalized Kadomtsev-Petviashvili modified equal width-Burgers equation, which is designated the propagation of long-wave with dissipation and dispersion in nonlinear media. To transform the given equation into a nonlinear ordinary differential equation, a traveling wave transformation has been carried out. As a result, we constructed distinct exact solutions like complex solutions, singular solutions, and complex singular solutions. Besides, 2D, 3D, and contour surfaces are illustrated to demonstrate the physical properties of the obtained solutions. © 2022. Natural Sciences Publishing Cor
Keywords: Analytical methods; Exact solutions; The (1/g? )-expansion method; The bernoulli sub-equation method; The generalized kp-mew-b equation